Oxygen, Gastrin-Releasing Peptide, and Pediatric Lung Disease: Life in the Balance - Mary E Sunday (Frontiers Media S.A., 2014)
Excessive oxygen (O2) causes tissue injury, scarring, aging, and even death. Our laboratory is studying O2-sensing pulmonary neuroendocrine cells (PNECs) and the PNEC-derived product gastrin-releasing peptide (GRP). Reactive oxygen species (ROS) generated from exposure to hyperoxia, ozone, or ionizing radiation (RT) can induce PNEC degranulation and GRP secretion. PNEC degranulation can also be induced by hypoxia, and effects of hypoxia are also mediated by free radicals. We have determined that excessive GRP mediates lung injury with acute and chronic inflammation, leading to pulmonary fibrosis (PF), triggered via ROS exposure or by directly treating mice with exogenous GRP. In animal models, GRP blockade abrogates lung injury, inflammation, and fibrosis. The optimal time frame for GRP blockade and the key target cell types remain to be determined. The concept of GRP as a mediator of ROS-induced tissue damage represents a paradigm shift about how oxygen can cause injury, inflammation, and fibrosis. The host PNEC response in vivo may depend on individual ROS sensing mechanisms and subsequent GRP secretion. Ongoing scientific and clinical investigations promise to further clarify the molecular pathways and clinical relevance of GRP in the pathogenesis of diverse pediatric lung diseases.